Some common dermatoses - American Academy of Dermatology; Institute for Dermatologic Communication and Education (New York : New York University Medical Center ; [Evanston, Ill. : for sale by the Academy], 1974)
Photographs of clinical examples of psoriasis, seborrheic dermatitis, pityriasis rosea, lichen planus, nummular eczema, dyshidrosis, atopic dermatitis, allergic contact dermatitis, acne, rosacea, alopecia areata, keloids, tinea corporis, tinea pedis, tinea unguium, tinea faciale, tinea versicolor, impetigo contagiosa, folliculitis, ecthyma, carbuncle, verruca vulgaris, verrucae planae, molluscum contagiosum, herpes simplex, and herpes zoster are presented. No written descriptions of the contents are provided.
Keywords: Skin diseases